2015
DOI: 10.1016/j.cell.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Slit and Receptor Tyrosine Phosphatase 69D Confer Spatial Specificity to Axon Branching via Dscam1

Abstract: SUMMARY Axonal branching contributes substantially to neuronal circuit complexity. Studies in Drosophila have shown that loss of Dscam1 receptor diversity can fully block axon branching in mechanosensory neurons. Here we report that cell-autonomous loss of the Receptor-Tyrosine-Phosphatase 69D (RPTP69D) and loss of midline-localized Slit inhibit formation of specific axon collaterals through modulation of Dscam1 activity. Genetic and biochemical data support a model in which direct binding of Slit to Dscam1 en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 49 publications
2
69
0
Order By: Relevance
“…All three Robo receptors are expressed in the brain in many different axonal tracts, but are specifically absent from the MB at the third instar larval stage (Figures S1L–S1W). While slit null mutant animals die at embryonic or early larval stages, we were able to examine the neuropil structure of viable slit mutants bearing a combination ( sli 2 / sli dui ) of a null allele ( sli 2 ) and a hypomorphic allele ( sli dui ) (Tayler et al., 2004) exhibiting a strong reduction of Slit in the larval and pupal nervous system (Dascenco et al., 2015). We found major defects in neuropil organization in several central brain areas, including MB lobes, the central complex, antennal lobes, and Robo2/Robo3-expressing axons in the developing brain (Figures 1I–1R).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three Robo receptors are expressed in the brain in many different axonal tracts, but are specifically absent from the MB at the third instar larval stage (Figures S1L–S1W). While slit null mutant animals die at embryonic or early larval stages, we were able to examine the neuropil structure of viable slit mutants bearing a combination ( sli 2 / sli dui ) of a null allele ( sli 2 ) and a hypomorphic allele ( sli dui ) (Tayler et al., 2004) exhibiting a strong reduction of Slit in the larval and pupal nervous system (Dascenco et al., 2015). We found major defects in neuropil organization in several central brain areas, including MB lobes, the central complex, antennal lobes, and Robo2/Robo3-expressing axons in the developing brain (Figures 1I–1R).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas physical interactions between RPTPs, including RPTP69d, and their substrates are known to be very transient and difficult to detect by co-immunoprecipitation (Dascenco et al., 2015, Flint et al., 1997) we were able to readily co-immunoprecipitate Robo3 and RPTP69d from S2 cells (Figures 6A–6C). RPTP69d-ΔC and RPTP69d-ΔN were also able to bind Robo3, indicating that the interaction may require the transmembrane and/or the juxtamembrane domain of RPTP69d.…”
Section: Resultsmentioning
confidence: 99%
“…As all four Dscam proteins are broadly expressed within the developing lamina, distinct paralogs, and isoforms of them, either alone or in combination may pattern dendrites in different ways. Furthermore, as Dscam proteins also interact with other proteins in both cis and trans (Andrews et al, 2008; Dascenco et al, 2015; Liu et al, 2009; Ly et al, 2008), they have the potential to pattern circuits in many different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, it was argued that the major role of Robo2 expressed in tendon cells is to fix cleaved Slit-N on tendon cells hence rendering it stable . A recent study also showed that Slit-N functions via Dscam1 (Down syndrome cell adhesion molecule 1), and independently of Robos, to regulate axon collateral extension of Drosophila mechanosensory neurons (Dascenco et al, 2015). In this context, the binding of Slit to Dscam1 leads to intracellular dephosphorylation of the receptor via the phosphatase RPTP69D (Ptp69D).…”
Section: The Proteolytic Processing Of Robo and Slitsmentioning
confidence: 99%
“…The Drosophila CNS midline has since served as a model for understanding Slit-Robo signaling. Nonetheless, it has become increasingly clear that axon guidance mechanisms, including those mediated by Slits and Robos, are not as evolutionarily conserved as previously assumed; evolution has led to the molecular diversification of axon guidance genes, thereby increasing crosstalk between different ligands and receptors (Dascenco et al, 2015;Delloye-Bourgeois et al, 2014;Wang et al, 2015;Zelina et al, 2014). Furthermore, it has emerged that the outcome of Slit-Robo interactions is highly context dependent, creating a multifunctional platform for cell-cell or cell-matrix interactions impacting multiple physiological and pathological processes.…”
Section: Introductionmentioning
confidence: 99%